(untitled) (Fiep Bulletin - online, 2013)
Introduction: The development and the childish learning are intrinsically connected to the mobility, showing fundamental for the global development of the child. A good motor control promotes appropriate exploration of environments, from concrete experiences. Aim: to verify the psychomotor profile of preschool in a particular school in the city of Lages/SC. Methodology: The population was composed of 20 preschools from 3 to 5 years of age, being 12 of masculine sex and 8 of the feminine sex, registered in a particular school in the city of Lages/SC. The inclusion criterion was signed by the TCLE by the parents/responsible for the child. The used instrument was Scale of Motor Development EDM (ROSA NETO, 2002). Results: The chronological age average was 4 years and 4 months. The general motor age of the sample was 5 years and 2 months, demonstrating a positive age of 10 months. The general motor quotient of the sample was classified as “superior”. The motor areas that had presented better resulted were global mobility and space organization; and the area with worse performance was the temporal organization. Conclusion: The components of the psychomotricity present different rhythms of development in each child, being that the preschool ones meet inside of the normality parameters. The necessity of accompaniment of these children stays evident in the long term, aiming at the maintenance of a good motor development.